PENGARUH JOB INSECURITY DAN SELF EFFICACY TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING: PADA PT MEGA INDAH SARI KABUPATEN GOWA - Nurhayati, Rika Mutiara Suci; Jafar, Akhmad (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study iams to determine the effect of job insecurity and self efficacy on employee performance through job statisfaction as an intervening variable at PT Mega Indah Sari. This study is a quantitative study collacted through a survey using a questionnaire. Data were processed using the partial least squares (PLS). Method and implemented using smart PLS 4. The results of this study indicate that job insecurity has a positive and significant effect on job insecurity has a positive and significant effect on employee performance, self efficacy has a positive and significant effect on employee performance, job saticfaction has a positive and significant effect on employee performance, job msecunty has a positive and significant effect on employee performance mediated by job satisfaction, and self efficacy has a positive and significant effect on employee performance mediated by job satisfaction Keywords: Job Insecurity, Self Efficacy, Employee Performance, Job Satisfaction